2013
DOI: 10.3109/15368378.2013.801352
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Health Effects of Living near Mobile Phone Base Transceiver Station (BTS) Antennae: A Report from Isfahan, Iran

Abstract: It is suggested that cellular phone BTS antenna should not be sited closer than 300 m to populations to minimize exposure of neighbors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…They found that the EMF intensity increased in the building and its surroundings after the MPBS installation. Shahbazi-Gahrouei [ 24 ] conducted a cross-sectional study on people living near the mobile phone base transceiver stations (BTS). The authors reported that discomfort, irritability, nausea, headache, dizziness, nervousness, depression, sleep disturbance, memory loss, and decreased libido were statistically significant among the people living near the BTS antenna (less than 300 m distant) compared to those living far from the BTS antenna (more than 300 m).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the EMF intensity increased in the building and its surroundings after the MPBS installation. Shahbazi-Gahrouei [ 24 ] conducted a cross-sectional study on people living near the mobile phone base transceiver stations (BTS). The authors reported that discomfort, irritability, nausea, headache, dizziness, nervousness, depression, sleep disturbance, memory loss, and decreased libido were statistically significant among the people living near the BTS antenna (less than 300 m distant) compared to those living far from the BTS antenna (more than 300 m).…”
Section: Discussionmentioning
confidence: 99%
“…Este hallazgo concuerda con lo reportado en otros estudios recientes de similar diseño en Alemania (19) e Irán (20), aunque en ellos la distancia entre la vivienda y las estaciones de telefonía móvil fue reportada por los propios participantes.…”
Section: Discussionunclassified
“…Furthermore, these symptoms are significantly higher in people living near mobile phone base-stations (<300 m), compared to those who live further from these (>300 m) [2].…”
Section: Introductionmentioning
confidence: 99%